Contextual Approach In Poetry Writing Training For Students - Idawati Garim; Kisman Salija; Suci Amaliah; Fadilah Neyarasmi (Tamaddun Life, 2024)
This study explores the effectiveness of a contextual approach in enhancing students’ poetry writing skills, creativity, and engagement at SMPN 1 Majene. By integrating students’ personal experiences and cultural contexts into the learning process, the study aimed to address challenges such as limited understanding of poetic structures, difficulties in self-expression, and lack of engagement in poetry writing. A qualitative descriptive method was employed, involving classroom observations, student artifacts, interviews, and reflective journals. The findings reveal that the contextual approach significantly improved students’ understanding of poetic elements such as rhyme, rhythm, and stanza structure. Furthermore, students demonstrated enhanced creativity and self-expression, producing authentic and emotionally resonant poems by drawing on their lived experiences. Collaborative activities, such as peer reviews and group discussions, fostered a supportive learning environment that further motivated students. However, challenges were observed, including difficulties with advanced poetic techniques and hesitancy in sharing work during peer sessions. These findings highlight the transformative potential of contextual learning in making poetry writing more accessible and meaningful, while also underscoring the need for ongoing refinement of teaching strategies. This study provides valuable insights for educators and curriculum designers seeking to enhance creative writing instruction through relevant and inclusive pedagogical approaches.